IMPLEMENTASI DEMOKRASI PANCASILA DALAM KEHIDUPAN BERNEGARA - Ramon Kaban (Perspektif, 2003)
Democracy of Pancasila as the realization of way of life, forming a group of community and state of Indonesian society, is a more concrete explanation of the Fifth Paragraph of Pancasila. Democracy of Pancasila Implementation combined with Pancasila ideology can be divided into unwritten basic law, systems of National Developmental Program (Propenas), and the subsequent activities, and more dominantly, systems of state decision making.